Sharia Hotel Management Policy: An Analysis of Islamic Attribute of Destination Theory in Indonesia and Malaysia - Qolbi, Fikri 'Ainul; Alam, Faizan; Rizka; Muthoifin (Journal of Islamic Economic Laws, 2024)
Islamic Destination Attributes play an essential role in influencing Muslim travelers' interests. This study analyses IAD by comparing Indonesia and Malaysia's current Islamic hotel policies. It was found that there are four dimensions of IAD, namely Worship Facilities, Islamic Facilities, General Islamic Facilities, and Halal Food, which are in accordance with Fatwa Number 108/DSN-MUI/X/2016 fifth article and MS 2610 2015 fourth and fifth articles. IAD is essential for Muslim hotel customer satisfaction. Both policies have fulfilled these four criteria. This study can contribute to academics and researchers in developing a more profound IAD theory. Although limited to the Islamic hotel sector, IAD studies can develop in other sectors with the same policy, such as travel agencies or tour guides.